2023
DOI: 10.7759/cureus.37846
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Its Impact on Healthcare Workers: Understanding Stigma, Stress, and Quality of Life

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has negatively impacted public health systems worldwide and created anxiety and stress among communities, resulting in the stigmatization of patients infected with the virus. Stigmatization of individuals who are sick or thought to be infected has a long history and can lead to discrimination and prejudice. This study aims to evaluate the prevalence of COVID-19-related stigma in Jordan, assess the relationship between stigma and the quality of life (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…This result is consistent with the multiple challenges and stressors faced by healthcare workers in their professional environment, such as the shortage of protective equipment during the early stages of the pandemic, time pressure to carry out tasks, losing colleagues to the disease, high rates of infection and death, and stress related to known and particularly unknown information (Gupta et al, 2021;Hall, 2020;Outeirinho et al, 2023). Research consistently reported the detrimental consequences of the pandemic in this specific population, namely adverse effects on mental health, with high rates of burnout, increased symptoms of stress, anxiety, and depression, and a negative impact on sleep and self-efficacy (Alhouri et al, 2023;Gupta et al, 2021;Hall, 2020;Outeirinho et al, 2023). The prevalence of workrelated dream themes in this population, including inefficiency, suggests that these environmental challenges "invaded" the oneiric life of healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the multiple challenges and stressors faced by healthcare workers in their professional environment, such as the shortage of protective equipment during the early stages of the pandemic, time pressure to carry out tasks, losing colleagues to the disease, high rates of infection and death, and stress related to known and particularly unknown information (Gupta et al, 2021;Hall, 2020;Outeirinho et al, 2023). Research consistently reported the detrimental consequences of the pandemic in this specific population, namely adverse effects on mental health, with high rates of burnout, increased symptoms of stress, anxiety, and depression, and a negative impact on sleep and self-efficacy (Alhouri et al, 2023;Gupta et al, 2021;Hall, 2020;Outeirinho et al, 2023). The prevalence of workrelated dream themes in this population, including inefficiency, suggests that these environmental challenges "invaded" the oneiric life of healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional survey has indicated that healthcare workers have showed a worsening in several aspects of their mental health during the COVID-19 pandemic, leading to increased risk of depressive symptoms, anxiety, and stress [70]. The intensity of the stress and anxiety symptomatology was dependent on the specialization of the healthcare personnel and the duration of exposure with individuals infected with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Made it extremely challenging for them to be able to balance the desire to sacrifice their safety and comfort to save lives oneself without compromising their health. It has also been reported that in some countries, health workers encountered stigma related to mental health struggles during the pandemic which deterred them from seeking support and hindered the development of a psychologically safe work environment [56,57].…”
Section: Health Workers' Application Of Servant Leadership In Their P...mentioning
confidence: 99%